The impact of immigration on the anxiety, self-esteem and attitudes towards school and friends of South African immigrant children : a thesis in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Mason, Lesleyanne (Massey University, 1997)
This study is an attempt to explore any psychological and emotional difficulties South African immigrant children may encounter in New Zealand. Use was made of both qualitative and quantitative data. Anxiety and self-esteem scales were administered together with various semantic differential examining attitudes towards and perceptions of friends and schools. Two questionnaires were designed to explore aspects of the South African children's immigration experience, including reasons for their immigration, how they feel about it, what they like and do not like about South Africa, and what they like and do not like about New Zealand. One of these questionnaires was completed by the South African children's parents and the other by the South African children. The sample consisted of 36 South African children who had volunteered from three North Shore Intermediate schools. The control group consisted of 36 New Zealand children who had volunteered from a North Shore Intermediate school. All of the children completed the anxiety, self-esteem scales and the semantic differentials. Only the South African children and their parents completed the questionnaires. Results indicated no significant difference in State and Trait anxiety and global self worth for South African children and New Zealand children based on gender. A significant difference was found in social acceptance for the New Zealand children based on gender. New Zealand girls have significantly higher self-esteem (social acceptance) than do New Zealand boys. South African immigrant children had significantly higher State anxiety than did New Zealand children. Anxiety and self- esteem was measured in relation to various demographic variables. It was found that South African immigrant children who knew another child at the first school attended in New Zealand had greater self-esteem (global self worth) than children who did not. South African immigrant children who were happy to be living in New Zealand had lower State anxiety and higher self-esteem (global self worth) than children who were not happy to be living in New Zealand. South African immigrant children have significantly more negative attitudes and perceptions of school in New Zealand than school in South Africa. They also have more negative attitudes and perceptions of their friends in New Zealand than New Zealand children have.
Keywords: Children of immigrants; New Zealand; Psychology; Self-esteem in children; Anxiety in children; South Africans